Navigating The Convergence Of Film And Multimedia Studies For Sustainable Communication Education In Digital Pace: Practitioners’ Perspectives - Chioma Rose CHIME-NGANYA; Timothy Ekeledirichukwu ONYEJELEM; Ifeany Martins NWOKEOCHA, PhD (International Journal of Education, Vocational and Social Science, 2026)
The relentless "digital pace" has dissolved the boundaries between cinematic arts and multimedia, yet higher education curricula often remain entrenched in obsolete silos. This pedagogical lag results in a disconnect between classroom instruction and the dynamic demands of the creative industries. Addressing this critical pedagogical lag, this study investigates the convergence of film and multimedia to analyse the extent of media convergence in professional practice; elicit practitioners’ perspectives on the essential skills required in the ‘digital pace’; and to propose a framework for sustainable communication education in Nigeria. The research is anchored on a triangulated theoretical foundation, synthesizing Jenkins’ Convergence Culture, Shaviro’s Post-Cinema Theory, and Onyejelem and Aondover’s Digital Generative Multimedia Tool Theory (DGMTT). Employing a triangulated-method, data were gathered from 150 purposively selected educators and media practitioners via online surveys and semi-structured interviews. Findings reveal a decisive consensus: 78% of practitioners deem the separation of these disciplines redundant, signaling an industrial shift from the traditional "cinematic shot" to the cross-platform "digital asset." Results also reveal that the data validates DGMTT, confirming that mastery of generative tools and AI is now a baseline requirement for employability. The study concludes that sustainability lies in embracing a "Post-Cinema" pedagogy that bridges the gap between high theory and technical application. Based on the findings of the triangulated approach, the study recommends restructuring curricula into a unified "Digital Media Arts" stream and establishing "Living Labs" to ensure classroom instruction mirrors the fluid, tool-driven reality of the modern creative economy.